2022
DOI: 10.1136/bmjopen-2021-060393
|View full text |Cite
|
Sign up to set email alerts
|

Preventing chronic disease in overweight and obese patients with low health literacy using eHealth and teamwork in primary healthcare (HeLP-GP): a cluster randomised controlled trial

Abstract: ObjectivesTo evaluate a multifaceted intervention on diet, physical activity and health literacy of overweight and obese patients attending primary care.DesignA pragmatic two-arm cluster randomised controlled trial.SettingUrban general practices in lower socioeconomic areas in Sydney and Adelaide.ParticipantsWe aimed to recruit 800 patients in each arm. Baseline assessment was completed by 215 patients (120 intervention and 95 control).InterventionA practice nurse-led preventive health check, a mobile applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 52 publications
0
21
0
1
Order By: Relevance
“…In this review, three types of fruit intake were reported, including servings/day in nine trials, 54,60,67,73,75,79,89,93,102 g/day in four trials, 56,65,94,101 and fruit intake scores in six trials, 62,77,87,97,99,103 involving 1283–4448 adults with overweight and obesity, as illustrated in Figure 5A–C. However, there were no significant differences ( p > 0.05) for the three types of fruit intake.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In this review, three types of fruit intake were reported, including servings/day in nine trials, 54,60,67,73,75,79,89,93,102 g/day in four trials, 56,65,94,101 and fruit intake scores in six trials, 62,77,87,97,99,103 involving 1283–4448 adults with overweight and obesity, as illustrated in Figure 5A–C. However, there were no significant differences ( p > 0.05) for the three types of fruit intake.…”
Section: Resultsmentioning
confidence: 98%
“…Our review found three types of vegetable intake such as servings/day, gram per day (g/day), vegetable intake scores in eight trials, 54,60,62,67,73,75,79,102 five trials, 56,65,93,94,101 and seven trials, 55,62,77,87,97,99,103 respectively, among 1365–2419 adults with overweight and obesity. Meta‐analyses showed that treatment intervention significantly ( t = 3.09, p = 0.012) improved vegetable intake (0.15 servings/day, 95% CI: 0.04, 0.26, PI 95% = 0.05, 0.25) with minimal effect ( g = 0.15) in Figure 4A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total 215 participants were recruited to the study (120 to the intervention group and 95 to the control group). The main outcomes of this study have been reported in Parker et al [ 17 ]. This nested study used qualitative interviews to elicit patient and provider perceptions and views regarding the receipt or delivery of weight management within the context of the HeLP-GP intervention.…”
Section: Introductionmentioning
confidence: 99%